17. yüzyıl Galata ve İstanbul Şer‘iyye Sicilleri’nde Bey‘Bi’l-İstiğlal akitleri - Denli, Mehmet Berkun (My University, 2018)
17. YÜZYIL GALATA VE İSTANBUL ŞER‘İYYE SİCİLLERİ’NDEBEY‘Bİ’L-İSTİĞLAL AKİTLERİOsmanlı araştırmalarında birincil kaynaklardan birisi olma özelliğini taşıyan şer‘iyye sicilleri; toplumsal, iktisadi ve hukuki alanlarda önemli bilgiler içerir. Bu çalışmada Osmanlı yaşamına ilişkin çok değerli bilgiler içeren bu kayıtlar üzerinden 17. yüzyıl Galata ve İstanbul sicil defterlerinde geçen bey‘bi’l-istiğlal akitleri hakkında bilgi sahibi olmak amaçlanmıştır. Bu amaç doğrultusunda ilk olarak İslâm hukukunda ribâ, karz ve hîle konuları açıklanmışdaha sonra bey‘ul-îne, muâmele-i şer‘iyye, bey‘i-bât, bey‘bi’l-vefâ, bey‘bi’l-istiğlal akitleri hakkında bilgiler verilmiştir. Bu bilgiler verildikten sonra 17. yüzyılda mahkeme defterlerinde geçen bey‘bi’l-istiğlal akitleri; tarafların kimlik bilgileri, akitlerin geçtiği mahalleler, tarafların din ve cinsiyet açısından değerlendirilmesi, akde konu olan mebî türleri, kira oranları, para birimleri ve mahkemelerdeki anlaşmazlıklar başlıkları tahlil edilmiştir.

BAY‘BI’L-ISTIGLAL CONTRACTS IN 17th CENTURY ISTANBULAND GALATA QADI COURT’S RECORDSQadi court’s records, which are one of the primary sources of Ottoman Studies, include important information related to social, economic and legal issues. In this study it is aimed to have information through these records, which contain unsubstituted information about the Ottoman life, about the bay‘bi’l-istiglal contracts mentioned in 17th century Galata and Istanbul courts registration. For this purpose, firstly, usury, loan and hîle (a way of getting around the law) issues have been explained according to the Islamic law, secondly information was given about bay‘al-inah (sale and buy-back), muâmele-i shariah (sale and buy-back), bay‘i-bât (sale), bay‘bi'l-vefâ (sale with power of redempti), bay‘bi'l-istiğlal (sale on the condition that the property becomes owners again after the seller fully paid back its price in rent to the buyer) contracts. Thirdly, the bay‘bi'l-istiğlal conventions mentioned in thecourt books in the 17th century has been analyzed under the headings: identities of contracting parties, the address of the property subject to contract, contracting parties, religion and gender of the parties, mebî (sold, offered for sale) kinds, rental rates, currency units, disagreement in the contracts.
Keywords: 17. Yüzyıl; Bay‘bi’l-istiglal contracts; Bey‘bi’l-istiğlal akitleri 17th Century; Court records; Courts, Islamic; Economic History; Ekonomi tarihi; History; Istanbul (Turkey); İstanbul (Türkiye); Mahkeme kayıtları; Mahkemeler, İslami; Osmanlı İmparatorluğu (1299-1918); Ottoman Empire (1299-1918); Qadi court’s records; Şer’iyye Sicilleri; Tarih; Turkey; Türkiye